Identification of dominant spoilage bacteria in sea cucumber protein peptide powders (SCPPs) and methods for controlling the growth of dominant spoilage bacteria by inhibiting hygroscopicity. (January 2021) - Li, Xinran; Yang, Ruiwen; Ju, Huapeng; Wang, Ke; Lin, Songyi
Abstract: Previous studies have found that high active sea cucumber peptide powders (SCPPs) have relatively significant hygroscopic properties. Problems such as liquefaction, altered taste, and decreased activity are observed owing to the hygroscopic nature of SCPPs. Therefore, to develop a new method for accurate, rapid analysis and identification of dominant spoilage bacteria due to hygroscopic SCPPs, we placed SCPPs in 75% RH and 25 °C to monitor the microbial genera and species in samples stored for 90 days in this highly hygroscopic environment. The antioxidant activity of SCPPs stored for 90 days was significantly lower than that of the nature SCPPs (P < 0.05). The hygroscopic nature of SCPPs resulted in the growth of dominant spoilage bacteria. Bacilli (45.89%) were the dominant bacteria at 5 days of storage in a highly hygroscopic environment. Bacilli (41.35%) and Gammaproteobacteria (40.96%) were the dominant bacteria at 15 days of storage in a highly hygroscopic environment, and the number of unidentified Cyanobacteria (20.06%) was sharply reduced to 0.04% (P < 0.05). The deterioration of SCPPs in the highly hygroscopic storage environment was related to Firmicutes and Proteobacteria, which mainly include Bacillus, Psychrobacter and Atopobium. Highlights: Explore the influence of moisture on the antioxidant activity of SCPPs by EPR. Investigate the changes of spoilage bacteria in SCPPs under the storage conditions. Volatile compounds in SCPPs were identified by a GC-MS flavor analyzer.